2016
DOI: 10.1161/jaha.115.002432
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes in Young Adulthood and Middle Age and Risk of Cardiovascular Disease and All‐Cause Mortality: The Doetinchem Cohort Study

Abstract: BackgroundThe associations between overall lifestyle profile and cardiovascular disease (CVD) and death have been mainly investigated in cross‐sectional studies. The full benefits of a healthy lifestyle may therefore be underestimated, and the magnitude of benefits associated with changes in lifestyle remains unclear. We quantified the association of changes in lifestyle profiles over 5 years with risk of CVD and all‐cause mortality.Methods and ResultsLifestyle factors (ie, diet, physical activity, smoking, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 35 publications
4
50
1
2
Order By: Relevance
“…22 In the current study, CVD end points included nonfatal and fatal occurrences of cerebrovascular events (stroke), coronary heart disease (CHD), and a combination of all manifestations of CVD (total CVD). Stroke comprised both hemorrhagic and ischemic stroke and was defined with the 9th (up to 1996) and 10th (from 1996 onward) editions of the International Classification of Diseases (ICD-9 and ICD-10, respectively) as follows: 430 to 438 (ICD-9) and I60-I67; I69; G45 (ICD-10).…”
Section: Cvd Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In the current study, CVD end points included nonfatal and fatal occurrences of cerebrovascular events (stroke), coronary heart disease (CHD), and a combination of all manifestations of CVD (total CVD). Stroke comprised both hemorrhagic and ischemic stroke and was defined with the 9th (up to 1996) and 10th (from 1996 onward) editions of the International Classification of Diseases (ICD-9 and ICD-10, respectively) as follows: 430 to 438 (ICD-9) and I60-I67; I69; G45 (ICD-10).…”
Section: Cvd Outcomesmentioning
confidence: 99%
“…Nonfasting total cholesterol and HDL-C levels were measured in ethylenediaminetetraacetic acid plasma (until 1998) or serum (from 1998 onward) at the Lipid Reference Laboratory using standardized enzymatic methods. 22 …”
Section: Covariatesmentioning
confidence: 99%
“…Reductions in mortality risk have been associated with smoking cessation,5 increases in physical activity6 7 and fruit consumption,7 8 but very few studies have examined changes in these behaviours combined. Of the two studies, one cohort study,9 and an analysis based on the control arm of a randomised colorectal screening trial,10 found that unhealthy changes in lifestyle (body mass index (BMI) <30 kg/m 2 ; non-smoking, physically active and a healthy diet) were associated with increases in mortality risk. For healthy changes, one study found the risk of mortality improved,10 whereas the other did not 9.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two studies, one cohort study,9 and an analysis based on the control arm of a randomised colorectal screening trial,10 found that unhealthy changes in lifestyle (body mass index (BMI) <30 kg/m 2 ; non-smoking, physically active and a healthy diet) were associated with increases in mortality risk. For healthy changes, one study found the risk of mortality improved,10 whereas the other did not 9. However, these studies characterised obesity, which is an established risk factor for mortality,11 as part of a healthy lifestyle and did not investigate the contribution of each component of lifestyle to the association with mortality.…”
Section: Introductionmentioning
confidence: 99%
“…the diet, the level of physical activity, discipline, alcohol intake, smoking etc.) has the biggest impact on health-its level of influence is as high as 50% [1][2][3][4][5][6]. Because this influence is so high, the aim of healthcare initiatives should be to raise the awareness of its importance and help in the development of a healthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%